Continuity and Change in European Cooperation during the Twentieth Century. (13th April 2018) - PATEL, KIRAN KLAUS; KAISER, WOLFRAM
Abstract : To sign the treaty creating the European Coal and Steel Community (ECSC) the foreign ministers of Belgium, France, the Federal Republic of Germany, Italy, Luxembourg and the Netherlands met in Paris in April 1951. In a solemn Joint Declaration they stressed that through the newly created organisation, 'the Contracting Parties have given their determination to set up the first supranational institution and thus lay the real foundations of an organised Europe'. The ministers represented the ECSC as a radical rupture with history, as if Europe had been completely disorganised until the new organisation's creation. In a similar vein, the ECSC Treaty emphasised the member states' resolution 'to substitute for historic rivalries a fusion of their essential interests; to establish, by creating an economic community, the foundation of a broad and independent community amongst peoples long divided by bloody conflicts'. Since 1951 official European Union (EU) documents and other sources have forged a similar image, one which has been undergirded by assumptions about the creation of the 'core Europe' of the ECSC as a collective 'supranational' break with a past characterised by severe ideological divisions and extreme nationalism.